2019
DOI: 10.1002/anie.201900141
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Organic Frameworks with Target‐Specific Active Sites Switched by Photoresponsive Motifs: Efficient Adsorbents for Tailorable CO2 Capture

Abstract: Photoresponsive metal–organic frameworks (PMOFs) are of interest for tailorable CO2 adsorption. However, modulation of CO2 adsorption on PMOFs is based on steric hindrance or structural change owing to weak interactions between CO2 and active sites. It is challenging to fabricate PMOFs with strong but tailorable sites for CO2 adsorption. Now, the construction of PMOFs with target‐specific (strong) active sites is achieved by introducing tetraethylenepentamine into azobenzene‐functionalized MOFs for tailorable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
100
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 184 publications
(102 citation statements)
references
References 57 publications
1
100
0
1
Order By: Relevance
“…Additional control experiments demonstrated that a 10% decrease in CO 2 uptake corresponds to 10 °C increase in the overall temperature of the sample. Similar effects, albeit more pronounced (>40%) were found for nonfluorinated azobenzene-decorated UiO-66(Zr) 108 and DMOFs 109 upon in situ exposure to UV-light and in mixed composite materials with polymers as secondary adsorbents 110 . The opposite effect following azobenzene E→Z isomerization on the uptake of CO 2 in a porous organic polymer decorated with pendant azobenzenes was reported by Zhang and coworkers.…”
Section: Gas Uptake Storage Separation and Releasesupporting
confidence: 61%
“…Additional control experiments demonstrated that a 10% decrease in CO 2 uptake corresponds to 10 °C increase in the overall temperature of the sample. Similar effects, albeit more pronounced (>40%) were found for nonfluorinated azobenzene-decorated UiO-66(Zr) 108 and DMOFs 109 upon in situ exposure to UV-light and in mixed composite materials with polymers as secondary adsorbents 110 . The opposite effect following azobenzene E→Z isomerization on the uptake of CO 2 in a porous organic polymer decorated with pendant azobenzenes was reported by Zhang and coworkers.…”
Section: Gas Uptake Storage Separation and Releasesupporting
confidence: 61%
“…Since the affinity of most MOFs toward CO 2 is rather low, Sun and co‐workers used an UiO‐66 MOF with AB side groups and embedded tetraethylenepentamine to increase the CO 2 affinity . Similar to a previous study by these authors in mesoporous silica, due to the attractive interaction between cis AB and the amine, the attractive CO 2 adsorptions sites were blocked upon photoisomerization.…”
Section: Photoswitchable Mofs From Photochromic Moleculesmentioning
confidence: 94%
“…Additionally, the π‐complexation‐based materials usually present limited stability especially when exposed to water and sulfides, 11,24 which is unfavorable for practical applications. By comparison, kinetic separation is considered as a more energy‐efficient way, as it provides the potential to achieve effective gas separation via mild physisorption interactions, which can greatly lower the energy cost to regenerate the adsorbents 25‐27 . However, there are only a handful of porous materials exhibiting really high efficiency for kinetics‐driven C 3 H 6 /C 3 H 8 separation, 3,28 because to precisely control over the pore size so as to match with the kinetic diameters of C 3 H 6 and C 3 H 8 is challenging.…”
Section: Introductionmentioning
confidence: 99%